Ancient DNA Research in Maritime and Underwater Archaeology: Pitfalls, Promise, and Future Directions. (14th January 2020) - Briggs, Lisa
The rapid progression of DNA technology allows for the application of recently developed techniques to an ever-growing body of archaeological and environmental material recovered from submerged archaeological sites. As NGS and DNA Capture replace PCR as the predominant method used to characterise DNA present within an archaeological sample, it is necessary to consider how this effects the possibilities for future research, but also gives cause to reconsider the findings of previously published work from PCR experiments on archaeological material from submerged sites. In this review, the pitfalls, promise, and future directions of ancient DNA research on archaeological material from coastal and maritime sites are discussed. Here, it is argued that a common stumbling block in past research has been a lack of characterisation of the deposition environment, and that this has obscured our understanding of DNA identified at submerged sites. Unique aspects of the marine environment may present further complications in our attempts to authenticate ancient DNA. Overcoming these challenges will significantly enhance our ability to confidently assign an archaeological origin to DNA isolated in artefacts, organic remains, and sediments from submerged archaeological sites.